Enhanced durability and tribological performance of polyvinyl alcohol/layered double hydroxide/tannic acid composites under repeated swelling cycles - Dieter Rahmadiawan; Shih-Chen Shi; Wei-Ting Zhuang; Eko Indrawan; Yolli Fernanda; Budi Syahri; Irzal Irzal (Universitas Negeri Padang, 2024)
In recent years, the exploration of polyvinyl alcohol (PVA) composites has garnered significant attention due to their versatility applications in aqueous environments. However, despite their promise, neat PVA exhibit limitations such as significant mechanical degradation under repeated swelling cycles. This study investigates the durability and tribological performance of polyvinyl alcohol (PVA) composites reinforced with nickel-iron layered double hydroxide (LDH) and tannic acid (TA) under repeated swelling cycles. Building on previous research that explored composite preparation and initial characterization, this research emphasizes the effects of cyclic swelling on wear resistance, friction behavior, and mechanical properties. Tribological tests were conducted to evaluate the coefficient of friction (COF) and wear rate before and after multiple swelling cycles, alongside tensile strength and strain measurements. The results revealed that the PVA/TA2/LDH2 composite, containing the highest additive content, exhibited the lowest wear rate of 11.52 × 10⁻⁵ mm³/Nm after 3 swelling cycles, demonstrating superior resistance to material degradation. Although PVA/TA2/LDH1 exhibited a slightly lower COF, its wear rate was higher due to reduced reinforcement. Compared to neat PVA, which showed a COF increase from 0.45 to 0.53, the PVA/LDH/TA composites retained their tribological stability, with only a marginal increase in COF and wear rate. Similarly, tensile strength of PVA/TA2/LDH2 decreased by only 11% after 3 cycles (from 33.3 MPa to 30 MPa), while neat PVA experienced a 25.5% reduction (from 30 MPa to 22.5 MPa). These findings highlight the potential of PVA/LDH/TA composites for applications in aqueous environments, offering significantly enhanced long-term performance and reliability.